Training at real and simulated altitude in swimming: Too high expectations? - Rodriguez, F. A. (Biomechanics and Medicine in Swimming XI, 2010)
INTRODUCTION: Altitude/hypoxic training (AT) is a common practice among swimmers although scientific evidence is scarce and its benefits remain controversial. This paper aims to overview current methods of AT and to discuss the scientific evidence on the effects and potential benefits on sea level swimming performance. METHODS: A systematic review of peer-reviewed scientific literature on AT for the improvement of swimming performance at sea level was conducted and results critically evaluated. RESULTS AND DISCUSSION: There is no evidence that training at natural altitude enhances swimming performance more than training at sea level. Based on research conducted in other sports, AT would require at least 3 to 4 weeks at 2100 to 2500 m of altitude to elicit a robust acclimatization response (primarily red cell mass increase) in the majority of athletes. The optimal approach is likely to be LH-TL, in which one "lives high" (i.e. 2100-2500 m) to get the benefits of altitude acclimatization and "trains low" (1250 m or less) to avoid the detrimental effects of hypoxic exercise. In fact, training at hypoxia does not appear to provide any physiologic advantage over normoxic exercise and might even impair performance. Whether the performance benefits would be similar for swimmers compared to other endurance trained athletes is not known and requires further research. Swimming performance enhancement by means of intermittent exposure to hypoxia is still controversial. However, it is likely that at least 12 h/day at 2100-3000 m for 3 to 4 weeks may suffice to increase red cell mass. Shorter exposure to more severe hypoxia (e.g. 4000 to 5500 m, 3 h/day for 2 to 4 weeks) combined with sea-level training may enhance VO2max, ventilatory threshold and middle-distance swimming performance after pre-competition tapering, although the mechanisms are unclear. In any case, there is substantial individual variability in the outcome of every AT strategy. Since none of these approaches has undoubtedly proven to enhance swimming performance, more research is warranted to clarify their effects and mechanisms. REFERENCES: 1. Truijens, M. J. & Rodríguez, F. A. (2010, in press). Altitude and hypoxic training in swimming. In: Seifert, L., Chollet, D. & Mujika, I., Swimming: Science and Performance. Hauppauge, New York: Nova Science Publishers. 2. Wilber, R. L. (2004). Altitude training and athletic performance. Champaign, Illinois: Human Kinetics.